The Model of Product Attributes and Brand Image : Purchase Decisions Based - Pertiwi, R. Dewi; Sudarso, Andriasan; Wardana, Wikrama; Agung, H. Syahrum; Ahidin, Udin; Haris Eko Prabowo, Faizal; Lenggogeni, Lenggogeni (International Journal of Advanced Multidisciplinary, 2023)
This study aimed to ascertain the following: consumer perceptions of Perhutani brand honey product attributes, brand image perception among consumers, factors that influence their decision to purchase Perhutani brand honey products, and the relationship between product attributes, brand image, and purchasing decisions. The study utilizes a descriptive survey method to depict variable behavior and an explanatory survey method to test hypotheses. Employing the causality research approach, the investigation focuses on the causative relationship between independent variables, such as product attributes and brand image, and purchasing decisions. The research analyzes the individual consumer/buyer of Perhutani brand Honey products at Ahmad Yani and Setiabudi Bandung outlets. This is a cross-sectional research, meaning data are gathered empirically from a sample of respondents to determine the population's views on the object of study. This study reveals that the interplay between product attributes, reference groups, and brand image significantly impacts sales. Specifically, the performance of product attributes and reference groups influences selling price trends, while product mix performance and reference groups impact brand image. Additionally, purchasing decisions are affected by the performance of the product mix and reference groups, which are influenced by selling price trends and brand image. It is important to note that there is a correlation between selling price trends and brand image, as well as between product mix performance and reference groups.